GOOD PRINCIPLES GOVERNANCE IN SETTLEMENT OF LAND POLLUTION DISPUTES: LEGAL AND SOCIOLOGICAL ANALYSIS - Haryasih, Siti (Communale Journal, 2023)
This research aims to analyze the implementation of good principle governance in resolving land pollution disputes, both from juridical and sociological aspects. The research methods used are normative juridical and empirical juridical, with a qualitative approach. Primary data was obtained from in-depth interviews with parties involved in land pollution disputes in Bogor Regency, West Java, while secondary data was obtained from documents and literature studies. The research results show that the implementation of the principles is exemplary. Governance in resolving land pollution disputes is still not optimal because there are still several obstacles, such as inconsistencies between applicable laws and regulations, lack of participation and transparency from the parties, low capacity and accountability of law enforcement officials, and weak supervision and assessment from the community. Therefore, this research recommends several steps to improve the implementation of the excellent principle governance in resolving land pollution disputes, including harmonization and synchronization of related laws and regulations, strengthening mechanisms for participation and transparency of the parties, increasing the capacity and accountability of law enforcement officials, as well as empowering the role and function of the community in monitoring and assessment.